Contact dermatitis associated with wearable cardioverter-defibrillator. Issue 5 (May 2022) - Kurokawa, Tasuku; Arimoto, Takanori; Hashimoto, Naoaki; Koyama, Kyoko; Watanabe, Ken; Kutsuzawa, Daisuke; Kato, Shigehiko; Watanabe, Tetsu; Yaguchi, Yoriko; Suzuki, Tamio; Watanabe, Masafumi
Abstract: A 51-year-old man with dilated cardiomyopathy was resuscitated from ventricular fibrillation. Twenty-days after using a wearable cardioverter-defibrillator (WCD) contact dermatitis with itching was evident and consistent with the self-gelling defibrillation electrodes patch on the back. Itching was controlled with clobetasol propionate application. The WCD was continued until catheter ablation and device implantation. The contact dermatitis was completely recovered two weeks after discontinuing the WCD. Among 58 patients using the WCD, three (5.2%) complained about discomfort with the device, and two (3.4%) complained of itching. Only the patient presented here (1.7%) suffered from contact dermatitis with itching. Contact dermatitis is rarely observed in patients wearing a WCD but physicians should be aware of this complication to maintain WCD compliance. <Learning objective: Inappropriate wearing of a wearable cardioverter-defibrillator (WCD) is sometimes related to an unfortunate clinical course. WCD compliance is of paramount importance since wearing it correctly can prevent a life-threatening arrhythmia. Contact dermatitis is rarely observed in patients wearing a WCD but physicians should be aware of this complication to maintain WCD compliance.>